Bibliography of Academic Writings and Relections on Social Science Research in Nepal - Onta, Pratyoush (Himalayan Journal of Sociology and Anthropology, 2011)
DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4674 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 177-205